Determinants and impacts of contract farming: Evidence from cultivation of onion, okra and pomegranate in Maharashtra, India - Kumar, Anjani; Roy, Devesh; Tripathi, Gaurav; Joshi, Pramod Kumar (Emerald Publishing Limited, 2025)
This study investigates the impact of contract farming in onion, okra and pomegranate production on profits of smallholder farmers in India. It also investigates the determinants of farmers’ participation in contract farming. The study is based on a survey of 1,131 farmers from Maharashtra, India engaged in the cultivation of these three crops.This study uses instrumental variable regressions and quasi-experimental methods to decipher the impact of contract farming.The study reveals that contract farming ensures higher returns for smallholders, enables their access to high-end markets and brings in risk-sharing with protection during price fluctuations. Farm size and farmers’ risk perceptions are significantly associated with their participation in contract farming.The study is based on cross-sectional data, which presents limitations on considering unobserved farmer-level individual heterogeneity.The study shows that contracts highlight the functioning of the contractor/integrator on both the input and output sides of the market. By providing better-quality inputs on credit and at discounted prices and by providing training, the integrator helps small farmers meet international food safety and quality standards, a historically difficult challenge for smallholders in India.